DOI: 10.17760/d20328916
|View full text |Cite
|
Sign up to set email alerts
|

Virtual human resource development in the United States Navy : a qualitative study of how Navy Service Members advance their professional knowledge through informal learning using Navy-related social media tools

Abstract: The purpose of this study was to explore how Navy active duty service members advance professional knowledge through informal learning using Navy-related social media tools. Two research questions were utilized: a. How do Navy service members advance their professional knowledge through informal learning by interacting with peers within Navy-related social media tools?, b. How do Navy service members advance their professional knowledge through informal learning interacting with digital objects within Navy-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 107 publications
(284 reference statements)
0
2
0
Order By: Relevance
“…Transfer of learning into VHRD, embedding learning from an external source into organizational systems, has at least three main types: proximal, intermediate, and distal (Bennett, 2010). Greenlund's (2019) aforementioned study found subtypes of intermediate transfer reported by Navy personnel, such as integrating new knowledge from social media to similar or more removed work contexts and systems. Transfer can stem from both formal learning and informal learning, which are fundamental learning processes defining VHRD (Bennett, 2009).…”
Section: Transfer Of Formal and Informal Learningmentioning
confidence: 87%
See 1 more Smart Citation
“…Transfer of learning into VHRD, embedding learning from an external source into organizational systems, has at least three main types: proximal, intermediate, and distal (Bennett, 2010). Greenlund's (2019) aforementioned study found subtypes of intermediate transfer reported by Navy personnel, such as integrating new knowledge from social media to similar or more removed work contexts and systems. Transfer can stem from both formal learning and informal learning, which are fundamental learning processes defining VHRD (Bennett, 2009).…”
Section: Transfer Of Formal and Informal Learningmentioning
confidence: 87%
“…Virtual human resource development shows that a dynamic relationship between culture and technology is isomorphic, or mutually influencing (Bennett, 2009(Bennett, , 2014b. For example, Greenlund's (2019) recent VHRD study found that Navy-related social media created a place for informal professional development that was characterized by a hybrid culture. The hybrid culture had many aspects of Navy culture as well as new facets that broke down traditional barriers of rank and hierarchy.…”
Section: Culture and Learning Communitymentioning
confidence: 99%